2008
DOI: 10.1152/ajplung.00529.2007
|View full text |Cite
|
Sign up to set email alerts
|

PDGF-induced human airway smooth muscle cell proliferation requires STAT3 and the small GTPase Rac1

Abstract: Simeone-Penney MC, Severgnini M, Rozo L, Takahashi S, Cochran BH, Simon AR. PDGF-induced human airway smooth muscle cell proliferation requires STAT3 and the small GTPase Rac1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 51 publications
9
62
0
Order By: Relevance
“…Consistent with this study, our results point to active Rac1 increasing IL6 production. In contrast to Faruqi et al, but similar to other previous reports (Simon et al, 2000;Simeone-Penney et al, 2008), Figure 5. Tripolide inhibits tumor formation in nude mice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with this study, our results point to active Rac1 increasing IL6 production. In contrast to Faruqi et al, but similar to other previous reports (Simon et al, 2000;Simeone-Penney et al, 2008), Figure 5. Tripolide inhibits tumor formation in nude mice.…”
Section: Discussionsupporting
confidence: 87%
“…Triptolide inactivated Rac1, a small GTPase in the Rho family that has clear roles in carcinogenesis. Rac1 is implicated in regulation of cell cycle regulators (Simeone-Penney et al, 2008), and we found that inhibition of Rac1 activation with a dominant negative allele reduced levels of CyclinD1 and CDK4. Thus, even if the evidence is indirect, a possible hypothesis for the G1 arrest seen when the colon carcinoma lines were treated with triptolide, is that active Rac1 was suppressed, leading to lower levels of cell cycle target genes.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…27 Plateletderived growth factor has been shown to regulate cell cycle progress by inducing Ccnd3 expression. 28,29 Thus, the observed low expression of Pdgfra after NAL treatment is consistent with the observed low expression of Ccnd3.…”
Section: Proliferation Of Progenitor Leydig Cellssupporting
confidence: 83%
“…Mechanical stress in airways can also induce EGF release from epithelial cells and thus contribute to remodeling (283). Emerging data suggest a role for the nonreceptor tyrosine kinase Abl, which appears to inhibit ERK1 phosphorylation, modulate actin dynamics, and further prevent the mitogenic effects of factors such as endothelin-1 and PDGF (138,139), the latter well known to be mitogenic in ASM (286). Other growth factors such as VEGF (187) and even the neurotrophin BDNF (5) can enhance ASM proliferation.…”
Section: L921mentioning
confidence: 99%